2019
DOI: 10.3233/rnn-190910
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal derived exosomes enhance recovery of motor function in a monkey model of cortical injury

Abstract: Background: Exosomes from mesenchymal stromal cells (MSCs) are endosome-derived vesicles that have been shown to enhance functional recovery in rodent models of stroke. Objective: Building on these findings, we tested exosomes as a treatment in monkeys with cortical injury. Methods: After being trained on a task of fine motor function of the hand, monkeys received a cortical injury to the hand representation in primary motor cortex. Twenty-four hours later and again 14 days after injury, monkeys received exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 75 publications
6
79
1
Order By: Relevance
“…Previous studies have demonstrated the efficacy of MSC-derived EVs in enhancing neurorestorative events including neurogenesis, angiogenesis, and axonal sprouting, both in vivo and in vitro in rodent and porcine models of brain injury and stroke (Xin et al 2012(Xin et al , 2013Chopp and Zhang 2015;Casado et al 2017;Williams et al 2019). Recently, we showed that systemic administration of MSC-EVs enhanced motor recovery in aged rhesus monkeys with cortical injury that involved damage to the hand representation of the primary motor cortex (Moore et al 2019). Compared to aged monkeys that received phosphate-buffered saline (PBS) vehicle, aged monkeys treated with EVs showed remarkable recovery, exhibiting full restoration of fine motor functionality within the first 3-5 weeks of recovery (Moore et al 2019).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Previous studies have demonstrated the efficacy of MSC-derived EVs in enhancing neurorestorative events including neurogenesis, angiogenesis, and axonal sprouting, both in vivo and in vitro in rodent and porcine models of brain injury and stroke (Xin et al 2012(Xin et al , 2013Chopp and Zhang 2015;Casado et al 2017;Williams et al 2019). Recently, we showed that systemic administration of MSC-EVs enhanced motor recovery in aged rhesus monkeys with cortical injury that involved damage to the hand representation of the primary motor cortex (Moore et al 2019). Compared to aged monkeys that received phosphate-buffered saline (PBS) vehicle, aged monkeys treated with EVs showed remarkable recovery, exhibiting full restoration of fine motor functionality within the first 3-5 weeks of recovery (Moore et al 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Brain tissue used in this study was from the nine aged female rhesus monkeys used in Moore et al 2019. They ranged in age from 16 to 26 years old (analogous to humans approximately 48 to 78 years old) (Tigges et al 1988).…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations